The cure among the Embera indigenous population: a social, cultural and physiological communication process - Alcaraz López, Gloria Margarita; Yagarí Tascón, Leopoldo (Investigación y Educación en Enfermería, 2008)
The article intends to analyse a cure act among embera culture and begin the approach of the comprehension of the therapeutics used by the shamán and to point out that, in the indigenous therapeutics, the dichotomy body - soul, individual-society-cosmos does not appear. The indigenous cure process, differs from the occidental one, it is a socio-cultural and physiological communication process; is an act that surpasses frontiers, since it allows the traditional medicine and the occidental one as well. All trough the article, is implicit that the traditional medicine, spite its lack of reputation and persecution suffered, remains alive among the group embera. key words: Indigenous, Ethomedicine, Jai, Chamán, Abreaction, Communication, Culture